[SKRIPSI] PENGARUH WAKTU TAHAN, TEMPERATUR, DAN MEDIA PENDINGIN TERHADAP PELEBURAN LIMBAH ALUMINIUM DENGAN METODE GRAVITY DIE CASTING - Satria, Darma; Gunawan, Indra; Sani, Almadora Anwar (MACHINERY Jurnal Teknologi Terapan, 2024)
Aluminum waste from practicum work in the CNC workshop and laboratory of Politeknik Negeri Sriwijaya is quite a lot and is wasted. This can cause pollution to the environment. Therefore, a casting process is carried out to reduce this impact, then the waste will be recycled again. Aluminum waste that has been recycled through the casting process can also become a product for reuse, especially in practical work in CNC workshops or laboratories. This casting is done using the gravity die casting method which uses a permanent mold to make it more efficient. To improve the casted product's quality, experiments are conducted. Three variables are used in this investigation, including melting temperatures of 700°C and 800°C., holding time in the mold: 10 minutes and 15 minutes, and quenching (cooling media: water and 20% brine). The methodology used in this research is Taguchi and Anova, which aims to find the influence and results of high hardness values to improve product quality. The highest hardness value result is with experimental temperature of 800℃, holding time of 10 minutes, and quenching of 20% salt water, which is 59.79 Kg/mm2.